2019
DOI: 10.3390/app10010042
|View full text |Cite
|
Sign up to set email alerts
|

Training of Deep Convolutional Neural Networks to Identify Critical Liver Alterations in Histopathology Image Samples

Abstract: Nonalcoholic fatty liver disease (NAFLD) is responsible for a wide range of pathological disorders. It is characterized by the prevalence of steatosis, which results in excessive accumulation of triglyceride in the liver tissue. At high rates, it can lead to a partial or total occlusion of the organ. In contrast, nonalcoholic steatohepatitis (NASH) is a progressive form of NAFLD, with the inclusion of hepatocellular injury and inflammation histological diseases. Since there is no approved pharmacotherapeutic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…The ReLU activation function is used to avoid the gradient of the loss with respect to weights generated in each layer as shown in Eq. (8).…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The ReLU activation function is used to avoid the gradient of the loss with respect to weights generated in each layer as shown in Eq. (8).…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In recent years Deep Convolutional Neural Network plays a major role in medical image analysis and proved to show better performances particularly, in cancer grading and classification problem. In [8] a deep CNN model was proposed to classify normal and abnormal non-alcoholic fatty liver disease. The proposed model was designed with three neural network layers for four class classification using Stochastic Gradient Descent (SGD) optimization technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ANN has been widely used in medical diagnosis applications as it dynamically adapts itself according to the training dataset. For liver diagnosis, ANNs have been extensively used by Rong-yun Mai et al [13] to diagnose liver cirrhosis with Hepatocellular Carcinoma, by Z. Xu to diagnose stage of cirrhosis [14] , by Alexandros Arjmand et al [15] to find out alterations in liver in Histopathology images , by D Santhosh Reddy et al [16] to diagnose and to categorize the ultrasound liver parenchyma texture into four different classes, by Cheng-Hsiung Wenga [19] to diagnose liver disease , Kawaguchi, T., Tokushige, K., Hyogo, H. et al [8] have done data mining analysis on the diagnosis of nonalcoholic fatty liver disease-related hepatocellular carcinoma and concluded that patients treated with hepatectomy and a serum albumin level ≥3.7 g/dLG in Japan have more survival rate. ZhenjieYao et al [17] have used densely deep learning model to detect liver disease.…”
Section: A Data Mining Models In Liver Disease Diagnosismentioning
confidence: 99%
“…CNNs have been used for different Histopathology tasks, like segmentation [ 48 , 49 ], detection of a specific image properties [ 50 ], and image grade classification [ 38 , 51 ]. Breast cancer tumour cellularity has also been addressed by deep techniques.…”
Section: Introductionmentioning
confidence: 99%